2016
DOI: 10.14814/phy2.12868
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins in ovine amnion: responses to altered amniotic fluid volumes and intramembranous absorption rates

Abstract: Aquaporins (AQPs) are transmembrane channel proteins that facilitate rapid water movement across cell membranes. In amniotic membrane, the AQP‐facilitated transfer of water across amnion cells has been proposed as a mechanism for amniotic fluid volume (AFV) regulation. To investigate whether AQPs modulate AFV by altering intramembranous absorption (IMA) rate, we tested the hypothesis that AQP gene expression in the amnion is positively correlated with IMA rate during experimental conditions when IMA rate and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Consistent with this concept is our recent finding that AQP1 expression in the ovine amnion was positively correlated with the rate of fluid transfer between the amniotic fluid compartment and fetal intramembranous vasculature, thus potentially participate in AFV regulation (Cheung et al. ).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with this concept is our recent finding that AQP1 expression in the ovine amnion was positively correlated with the rate of fluid transfer between the amniotic fluid compartment and fetal intramembranous vasculature, thus potentially participate in AFV regulation (Cheung et al. ).…”
Section: Introductionsupporting
confidence: 59%
“…In ovine amnion, AQP8 mRNA level is highest while AQP9 is lowest when compared to AQP1, AQP3 and AQP11 levels (Cheung et al. ). Whether such differences would alter amniotic fluid dynamics is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies were similar to those recently described (Cheung et al. ). Single strand cDNA synthesis from total RNA (2 μ g) was carried out using MultiScribe reverse transcriptase and random primers in the presence of RNase inhibitor (Applied Biosystems, Life Technologies, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental protocols were described elsewhere (Cheung et al. ). Tissues were collected 2 days after initiating one of four different experimental conditions: control, urine drainage without fluid replacement, urine drainage with isovolumic fluid replacement (lactated Ringer's solution), and continuous intra‐amniotic fluid infusion (2 L/day of lactated Ringer's solution).…”
Section: Methodsmentioning
confidence: 99%
“…In animal studies, the effect of fetal urinary prostaglandin E 2 on IM transport was explored but results did not support such a role (Cheung, Beardall, Anderson, & Brace, ). Conversely, AQP1 appeared to play a positive role in regulating the rate of IM transport (Cheung, Anderson, & Brace, ) while the growth and permeability factor vascular endothelial growth factor (VEGF) may mediate amniotic fluid transport across the amnion (Cheung, Anderson, & Brace, ). Recently, we reported that IM transport across the amnion is a multifactorial regulatory process that involves cellular transport pathways and signaling modulators.…”
Section: Introductionmentioning
confidence: 99%